Dryland Social-Ecological Systems in Changing Environments - Fu, Bojie; Stafford-Smith, Mark.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book prepared by a joint working group committed to critical research on dryland social-ecological systems (SESs) presents a timely synthesis of up-to-date knowledge in various thematic fields relevant to dryland SESs. It aims to organize key salient concepts and establish a conceptual framework relevant to the interdisciplinary and cross-cultural understanding of dryland SESs, which have specific contexts and a geographically representative structure. Through synthesizing research across the world and analyzing scientific evidence for good practices, it has the potential to promote collaboration among global researchers as well as communication with policy makers, managers, and practitioners for dryland ecosystem management to promote sustainability. It calls for synergies between different sectors and countries to achieve Sustainable Development Goals in drylands. .
The Global-DEP: A research programme to promote sustainability of dryland social-ecological systems -- Dryland dynamics and driving forces -- Structure, functions, and interactions of dryland ecosystems -- Dryland ecosystem services and human wellbeing in a changing environment and society -- Ecosystem Management and Sustainable Livelihoods in Drylands.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Physical geography; Sustainability; Bioclimatology; Water; Hydrology; Physical Geography; Sustainability; Climate Change Ecology; Water; Earth System Sciences